Two Nothofagus Species in Southernmost South America Are Recording Divergent Climate Signals - Pamela Soto-Rogel; Juan Carlos Aravena; Ricardo Villalba; Christian Bringas; Wolfgang Jens-Henrik Meier; Álvaro Gonzalez-Reyes; Jussi Grießinger (Forests, 2022)
Recent climatic trends, such as warming temperatures, decrease in rainfall, and extreme weather events (e.g., heatwaves), are negatively affecting the performance of forests. In northern Patagonia, such conditions have caused tree growth reduction, crown dieback, and massive die-back events. However, studies looking at these consequences in the southernmost temperate forest ( Nothofagus betuloides and Nothofagus pumilio ) are much scarcer, especially in southernmost South America (SSA). These forests are also under the influence of the positive phase of Antarctic Oscillation (AAO, also known as Southern Annular Mode, SAM) that has been associated with increasing trends in temperature, drought, and extreme events in the last decades. This study evaluated the growth patterns and the climatic response of eight new tree-ring chronologies from Nothofagus species located at the upper treeline along different environmental gradients in three study areas: Punta Arenas, Yendegaia National Park, and Navarino Island in SSA. The main modes of the ring-width index (RWI) variation were studied using principal component analysis (PCA). We found that PC1 has the higher loadings for sites with precipitation values over 600 mm/yr, PC2 with N. betuloides sites, and PC3 with higher loadings for sites with precipitation values below 600 mm/yr. Our best growth-climate relationships are between N. betuloides and AAO and the most northeastern site of N. pumilio with relative humidity (which coincides with heatwaves and extreme drought). The climatic signals imprinted in the southernmost forests are sensitive to climatic variability, the climate forcing AAO, and the effects of climate change in the last decades.